Effect of co-inoculation with growth-promoting bacteria and arbuscular Mycorrhizae on growth of Persea americana seedlings infected with Phytophthora cinnamomi - Solórzano Acosta, Richard Andi (2024)
Avocado is one of the most in-demand fruits worldwide and the trend towards its sustainable production, regulated by international standards, is increasing. One of the most economically important diseases is root rot, caused by Phythopthora cinnamomi. Regarding this problem, antagonistic microorganism use is an interesting alternative due to their phytopathogen control efficiency. Therefore, the interaction of arbuscular mycorrhizal fungi of the phylum Glomeromycota, native to the Peruvian coast (GWI) and jungle (GFI), and avocado rhizospheric bacteria, Bacillus subtilis and Pseudomonas putida, was evaluated in terms of their biocontrol capacity against P. cinnamomi in the “Zutano” variety of avocado plants. The results showed that the GWI and Bacillus subtilis combination increased the root exploration surface by 466.36%. P. putida increased aerial biomass by 360.44% and B. subtilis increased root biomass by 433.85%. Likewise, P. putida rhizobacteria showed the highest nitrogen (24.60 mg ∙ g−1 DM) and sulfur (2.60 mg ∙ g−1 DM) concentrations at a foliar level. The combination of GWI and Bacillus subtilis was the treatment that presented the highest calcium (16.00 mg ∙ g−1 DM) and magnesium (8.80 mg ∙ g−1 DM) concentrations. The microorganisms’ multifunctionality reduced disease severity by 85 to 90% due to the interaction between mycorrhizae and rhizobacteria. In conclusion, the use of growth promoting microorganisms that are antagonistic to P. cinnamomi represents a potential strategy for sustainable management of avocado cultivation.